2018
DOI: 10.1111/pbi.12868
|View full text |Cite
|
Sign up to set email alerts
|

Allele exchange at the EPSPS locus confers glyphosate tolerance in cassava

Abstract: SummaryEffective weed control can protect yields of cassava (Manihot esculenta) storage roots. Farmers could benefit from using herbicide with a tolerant cultivar. We applied traditional transgenesis and gene editing to generate robust glyphosate tolerance in cassava. By comparing promoters regulating expression of transformed 5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS) genes with various paired amino acid substitutions, we found that strong constitutive expression is required to achieve glyphosate tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 26 publications
1
86
0
Order By: Relevance
“…This genetic transformation event (GA21), however, included a strong promoter with three TIPS EPSPS gene copies in tandem (Monsanto, ). Indeed, it has been shown that the fitness cost observed in transgenic, glyphosate‐tolerant cassava ( Manihot esculenta ) plants with the double EPSPS mutation can be compensated for by EPSPS overexpression via a strong CRISPR/Cas9‐edited promotor (Hummel et al ., ). This means of rescuing plants with a fitness cost will remain as a working hypothesis, however, until EPSPS double mutations and overexpression are identified in single, naturally evolved plants displaying no fitness cost.…”
Section: Evolutionary Rescue Of Fitness Costsmentioning
confidence: 97%
See 1 more Smart Citation
“…This genetic transformation event (GA21), however, included a strong promoter with three TIPS EPSPS gene copies in tandem (Monsanto, ). Indeed, it has been shown that the fitness cost observed in transgenic, glyphosate‐tolerant cassava ( Manihot esculenta ) plants with the double EPSPS mutation can be compensated for by EPSPS overexpression via a strong CRISPR/Cas9‐edited promotor (Hummel et al ., ). This means of rescuing plants with a fitness cost will remain as a working hypothesis, however, until EPSPS double mutations and overexpression are identified in single, naturally evolved plants displaying no fitness cost.…”
Section: Evolutionary Rescue Of Fitness Costsmentioning
confidence: 97%
“…Studies on the molecular biology and physiology of glyphosate resistance in several weed species have contributed to a broader and deeper understanding of herbicide resistance evolution. For evolved glyphosate‐resistant weeds, resistance mechanism studies reveal EPSPS gene amplification (Gaines et al ., a; Jugulam et al ., ; Patterson et al ., ) through the inheritance of replicating extrachromosomal circular DNA molecules (Koo et al ., ,b), EPSPS transcriptional regulation (Zhang et al ., ), EPSPS double mutants (Funke et al ., ; Sammons & Gaines, ; Chen et al ., , ; Yu et al ., ; Sauer et al ., ; Hummel et al ., ; Sammons et al ., ) and vacuolar sequestration of glyphosate via ABC transporters, with the dependence of this process on light (Sharkhuu et al ., ) and temperature (Ge et al ., ). The substantial research effort that continues to reveal glyphosate resistance mechanisms/mutations reflects that glyphosate is the most globally used herbicide and highlights the intriguing evolutionary pathways used by weed species to resist glyphosate.…”
Section: Scope Of This Reviewmentioning
confidence: 98%
“…In controlled experiments, the same group later confirmed the extreme fitness penalty imposed by the TIPS mutations (34). Similarly, unacceptable agronomics were observed in cassava edited to create the TIPS or TIPA mutations, unless highly expressed by a constitutive viral promoter (35,36). Furthermore, homozygosity for TIPS where the T0 rice plants were produced by CRISPR/Cas9 gene editing could not be found among 93 T2 plants analyzed, and was suggested to be lethal (37).…”
Section: Combinations Involving Thr 102 and Pro 106 Could Not Be Furtmentioning
confidence: 88%
“…Aside from the amazing potential for gene editing as a diagnostic tool and perhaps even a treatment for many debilitating diseases (Ortiz-Virumbrales et al 2017;Reczek et al 2017;Zabinyakov et al 2017), the potential possible uses of this technology in plants and livestock animals is similarly impressive (Lamas-Toranzo et al 2017). Creation of disease-resistant and less allergenic food crops (Hummel et al 2018;García-Molina et al 2019) with enhanced nutrient profiles (Wang et al 2019) is now within our reach; the future implications for feeding a progressively larger world population are immense.…”
Section: Discussionmentioning
confidence: 99%